2022
DOI: 10.1108/oir-02-2022-0082
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 fake news among the general population: motives, sociodemographic, attitude/behavior and impacts – a systematic review

Abstract: PurposeThis systematic review aims to synthesize the literature reporting the motives, sociodemographic, attitude/behavior and impacts of fake news during the COVID-19 pandemic, targeting the general population worldwide.Design/methodology/approachA systematic review approach was adopted based on PRISMA, targeting articles published in five databases from January 2020 to November 2021. The screening resulted in 46 eligible papers.FindingsResults indicate low level of awareness, knowledge, media/health literacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The results indicate that FI negatively moderates the mediation process, reflecting FI's complex roles in China's health misinformation setting. Compared with the extensive literature regarding health misinformation sharing among the general population amidst COVID-19 (Balakrishnan et al, 2022), this study offers empirical evidence about health misinformation dissemination among a specific age group in normal settings. The findings additionally shed light on online health misinformation regulation in aging societies such as China.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that FI negatively moderates the mediation process, reflecting FI's complex roles in China's health misinformation setting. Compared with the extensive literature regarding health misinformation sharing among the general population amidst COVID-19 (Balakrishnan et al, 2022), this study offers empirical evidence about health misinformation dissemination among a specific age group in normal settings. The findings additionally shed light on online health misinformation regulation in aging societies such as China.…”
Section: Discussionmentioning
confidence: 99%
“…For example, false news stories about the safety of vaccines have been shown to negatively impact vaccination rates, resulting in serious public health consequences (Wilson and Wiysonge, 2020). Researchers have examined the impacts of fake news during the COVID-19 pandemic, revealing negative impacts of fake news dissemination that include violation of precautionary measures and low trust in government and news (Balakrishnan et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Especially as they have not been subject to the same type of historical trauma and economic deprivation as many of the other socio-economic and cultural groupings involved. Some research has argued that the conspiracy community is made up of rural uneducated people with low socio-economic status (Balakrishnan et al, 2023). However, this over-generalisation is generally considered to be factually incorrect, instead, Bloom & Moskalenko (2021) found that an individual's socio-economic position is not a consistent predictor of conspiracy beliefs.…”
Section: Personal Strainmentioning
confidence: 99%